2000
DOI: 10.1152/ajpendo.2000.279.4.e752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PDH activation by dichloroacetate in human skeletal muscle during exercise in hypoxia

Abstract: During the onset of exercise in hypoxia, the increased lactate accumulation is associated with a delayed activation of pyruvate dehydrogenase (PDH; Parolin ML, Spreit LL, Hultman E, Hollidge-Horvat MG, Jones NL, and Heigenhauser GJF. Am J Physiol Endocrinol Metab 278: E522-E534, 2000). The present study investigated whether activation of PDH with dichloroacetate (DCA) before exercise would reduce lactate accumulation during exercise in acute hypoxia by increasing oxidative phosphorylation. Six subjects cycled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 37 publications
10
54
1
Order By: Relevance
“…Faster V O 2p kinetics, reflecting faster activation of mitochondrial oxidative phosphorylation and muscle O 2 utilization (2, 21, 38) is expected to reduce the requirement for substratelevel phosphorylation (and nonoxidative ATP synthesis), thereby lowering PCr breakdown and lactate accumulation during the exercise transition (7,31,40,46,53). In the present study, PCr breakdown was reduced in Mod 2 compared with Mod 1 (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Faster V O 2p kinetics, reflecting faster activation of mitochondrial oxidative phosphorylation and muscle O 2 utilization (2, 21, 38) is expected to reduce the requirement for substratelevel phosphorylation (and nonoxidative ATP synthesis), thereby lowering PCr breakdown and lactate accumulation during the exercise transition (7,31,40,46,53). In the present study, PCr breakdown was reduced in Mod 2 compared with Mod 1 (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…However, the role of PDH activation in constraining the increase in oxidative metabolism, and therefore muscle O 2 utilization and V O 2p kinetics, is controversial. Several studies have demonstrated a decrease in substrate-level phosphoryla- tion consistent with faster adjustment of oxidative phosphorylation during exercise following pharmacological activation of PDH by dichloroacetate (DCA) (31,40,53), but other studies failed to demonstrate faster V O 2p kinetics following administration of DCA (34b, 37, 47). While these latter results are not consistent with PDH activation playing a significant role in constraining V O 2p kinetics, it is noteworthy that in these studies, PDH activation was not measured, and the studies were conducted on young healthy adults having relatively fast V O 2p kinetics, where a delay to fully activate PDH has not been observed under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies treated patients with DCA and directly measured PDH activity in muscle biopsies. Dichloroacetate administered at 35 -50 mg kg À1 decreases lactate levels by more than 60% and directly activates PDH by 3 -6 fold (Howlett et al, 1999;Parolin et al, 2000).…”
Section: Dca: Mechanism Of Action and Clinical Experiencementioning
confidence: 99%
“…However, Gibala, MacLean, Graham & Saltin, (1998) Dichloroacetate infusion results in near-maximal activation of the pyruvate dehydrogenase complex and stockpiling of acetyl-units. During the transition to subsequent moderate intensity exercise, dichloroacetate infusion has consistently been shown to enhance the rate of increase of oxidative metabolism as indicated by a reduction in phosphocreatine degradation and lactate accumulation (Timmons et al 1996;Timmons, Poucher, Constantin-Teodosiu, Macdonald & Greenhaff, 1997;Timmons et al 1998aTimmons, Gustafsson, Sundberg, Jansson & Greenhaff, 1998bHowlett, Heigenhauser, Hultman, Hollidge-Horvat & Spriet, 1999a;Parolin et al 2000;Roberts, Loxham, Poucher, Constantin-Teodosiu & Greenhaff, 2002).…”
Section: Introductionmentioning
confidence: 99%